PERAN NOTARIS DALAM PROSES PENGADAAN TANAH UNTUK PERUMAHAN OLEH CV. TERBIT JAYA DI KOTA PRABUMULIH - , FEBRI EKARASTI, Dr. Djoko Sukisno, SH., CN. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purposes of the research which is entitled âThe Function of Notary Public in Land Acquisition for Housing by CV. Terbit Jaya in Prabumulihâ are to identify the process of land acquisition for housing and identify the function of notary public in land acquisition for housing by CV. Terbit Jaya in Prabumulih. This research was done by using legal normative-empirical approach. Researchâs subject were respondents and resource persons that specified with non probability sampling techniques using purposive sampling. The data which were used in this research were the primary data and secondary data consisting of primary legal data, secondary legal data, and tertiary legal data. The data were collected through the library research by documents study and field research by interview, then the data were analyzed qualitatively by descriptive methods. The results of this research indicate that there are two ways in acquisiting the land for housing by CV. Terbit Jaya in Prabumulih. The ways are by making a contract of cooperation which is legalized by notary public and contract of sale which is made underhand by the parties. The function of notary public in land acquisition for housing by CV. Terbit Jaya in Prabumulih are legalizazing the contract of cooperation, making power of attorney for the sale of the land and power of attorney for land fission based on underhand contract of sale.